Formation of naringin and naringenin particles in supercritical medium and evaluation of biological activities in vitro and in vivo - Oliveira, Patricia Viera de (2024)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2024.